Association of sex and cardiovascular risk factors with atherosclerosis distribution pattern in lower extremity peripheral artery disease - Baretella, Oliver; Buser, Laura; Andres, Claudine; Häberli, Dario; Lenz, Armando; Döring, Yvonne; Baumgartner, Iris; Schindewolf, Marc (Frontiers in Cardiovascular Medicine, 2023)
Background: Atherosclerosis expression varies across coronary, cerebrovascular and peripheral arteries, but also within the peripheral vascular tree. The underlying pathomechanisms of distinct atherosclerosis phenotypes in lower extremity peripheral artery disease (PAD) is poorly understood. We investigated the association of cardiovascular risk factors (CVRF) and atherosclerosis distribution in a targeted approach analysing symptomatic patients with isolated anatomic phenotypes of PAD. Methods:In a cross-sectional analysis of consecutive patients undergoing first-time endovascular recanalisation for symptomatic PAD, data of patients with isolated anatomic phenotypes of either proximal (iliac) or distal (infrageniculate) atherosclerosis segregation were extracted. We performed a multivariate logistic regression model with backward elimination to investigate the association of proximal and distal PAD with CVRFs. Results: Of 637 patients (29% women) with endovascular recanalisation, 351 (55%) had proximal, 286 (45%) distal atherosclerosis. Female sex (OR 0.33, 95% CI 0.20 to 0.54, p = .01), active smoking (OR 0.16, 95% CI 0.09 to 0.28, p < .001), and former smoking (OR 0.33, 95% CI 0.20 to 0.57, p < .001) were associated with proximal disease. Diabetes mellitus (DM) (OR 0.33, 95% CI 1.06 to 1.61 p = .01), chronic kidney disease (CKD) (OR 1.18, 95% CI 1.08 to 1.28, p < .001), and older age (OR 1.31, 95% CI 1.06 to 1.61, p = .01) were associated with distal disease. Conclusions: Female sex, particularly in the context of smoking, is associated with clinically relevant, proximal atherosclerosis expression. Our additional findings that distal atherosclerosis expression is associated with DM, CKD and older age suggest that PAD has at least two distinct atherosclerotic phenotypes with sex-specific and individual susceptibility to atherogenic risk factors